BDNF-induced nitric oxide signals in cultured rat hippocampal neurons: time course, mechanism of generation, and effect on neurotrophin secretion - Kolarow, Richard; Kuhlmann, Christoph R. W.; Munsch, Thomas; Zehendner, Christoph; Brigadski, Tanja; Luhmann, Heiko J.; Lessmann, Volkmar (Frontiers in Cellular Neuroscience, 2014)
BDNF and nitric oxide signaling both contribute to plasticity at glutamatergic synapses. However the role of combined signaling of both pathways at the same synapse is largely unknown. Using NO imaging with diaminofluoresceine in cultured hippocampal neurons we analyzed the time course of neurotrophin induced NO signals. Application of exogenous BDNF, NT-4, and NT-3 (but not NGF) induced NO signals in the soma and in proximal dendrites of hippocampal neurons that were sensitive to NO synthase activity, TrkB signaling, and intracellular calcium elevation. The effect of NO signaling on neurotrophin secretion was analyzed in BDNF-GFP and NT-3-GFP transfected hippocampal neurons. Exogenous application of the NO donor sodium-nitroprusside markedly inhibited neurotrophin secretion. However, endogenously generated NO in response to depolarization and neurotrophin stimulation, both did not result in a negative feedback on neurotrophin secretion. These results suggest that a negative feedback of NO signaling on synaptic secretion of neurotrophins operates only at high intracellular levels of nitric oxide that are under physiological conditions not reached by depolarization or BDNF signaling.